Local Mexico: Democratic Transitions in an Authoritarian Context - Olney, Patricia (FirstForumPress, a division of Lynne Rienner Publishers, Inc., 2018)
Keywords: Local government; Mexico; dept.psc; faculty_collection

The post Cold war reestablishment of effective state authority in Latin America: can 'colombianization' tame Mexico's security crisis? - Olney, Patricia (Social Science Research Network, 2009)
This paper explores the Post Cold War origins of the organized criminal violence that once gripped Colombia and now grips Mexico and particularly the highly controversial counterinsurgency strategy used in Colombia that forms the basis for the current strategy in Mexico. It argues that ideology is a reason why the military aspect of these problems was neglected for so long and the reason its detractors see it as a strategy that reduces national sovereignty and endangers democracy when statistics on control of territory, reduction of violence and democratic progress demonstrate the opposite to be true. The paper uses the term “colombianization” to emphasize Colombia’s dramatic shift from almost ungovernable to one of the most stable countries in the region. Colombianization is defined not as a counterdrug strategy as are both the Colombian and Mexican U.S. assistance strategies but as an integrated, law-based, counterinsurgency strategy implemented from the bottom up that facilitates the establishment of elite consensus and puts the country on a path toward rule of law. Ironically, it was democratic and free market reforms that strengthened the forces of instability in both Colombia and Mexico and the militarization of security that appears to facilitate democratic stability. This study uses local level assessments of Plan Colombia and local interviews conducted in Chihuahua and Michoacán to evaluate the prospects of colombianization in urban and rural Mexico. Colombia's experience suggests that colombianization can stabilize the country and help reactivate the economy but democratic progress is painfully slow and the strategy has little impact on the drug industry and the corruption associated with it.
Keywords: Patricia Olney; SSRN; The Post Cold War Reestablishment of Effective State Authority in Latin America: Can 'Colombianization' Tame Mexico's Security Crisis?; dept.psc; ⛔ No DOI found